PREREQUISITES FOR EFFECTIVE ENGLISH LANGUAGE LEARNING - Useini, Arafat (International Scientific Journal Vision, 2025)
Communicating in multiple languages is becoming increasingly valuable in our interconnected and globalized world. However, knowing grammar and the alphabet does not necessarily mean one can pronounce words correctly. Learning pronunciation rules from the beginning helps overcome initial obstacles and proves beneficial in the long run. Practicing pronunciation and being mindful of it while learning a language is essential for fluency. This article explores the necessity of learning a foreign language, emphasizing cognitive benefits, career opportunities, cultural appreciation, and social advantages. Additionally, it discusses the challenges learners face and strategies to overcome them. Learning a new language can seem intimidating, but with the right mindset, methods, and motivation, anyone can achieve fluency. The key is to approach language learning with optimism and self-belief. Instead of dwelling on negative thoughts such as “I’m not good at languages” or “I tried before and failed”, learners should focus on incremental progress. With consistent effort over time, fluency is within reach. To achieve success in learning English as a foreign language, it is essential to lay a strong foundation with certain prerequisites. These foundational elements help learners progress more effectively and efficiently in their language-learning journey.